PELATIHAN PEMBUATAN SABUN BATANG DARI LIMBAH MINYAK JELANTAH DENGAN TEKNIK PENJERNIHAN MENGGUNAKAN MINERAL BENTONIT BAGI SISWA SMAN 23 BANDUNG - Meirawati, Mira; Rendy; Yuda, Himmes Fitra; Adhitama, Ramadhan; Rachmawan, Sigit (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
Earth science remains relatively unpopular among the general public as a fundamental discipline. School learning relies heavily on rote memorization, leaving little room for exploration and real-life application of earth science concepts. However, geology is crucial in human life, encompassing multidimensional knowledge relevant to sustainable living and utilizing natural resources. To promote the importance of earth science in daily life, a Community Service (PkM) activity was conducted involving students from SMAN 23 Bandung, located in the densely populated area of Antapani, Bandung. The PkM activity focuses on the role of bentonite clay minerals as a clarifier for used cooking oil and as an adsorbent material in facial masks. Training on using bentonite minerals was provided to enable participants to apply them in their daily activities. The evaluation of questionnaires and interactive discussions showed that the PkM successfully increased awareness and provided education about the benefits of bentonite clay in purifying used cooking oil and its application as a soap-making material. Questionnaires given to 20 participants from SMAN 23 Bandung highlighted the importance of socializing environmentally friendly and health-safe earth science concepts. Adopting an integrated approach using locally available bentonite materials to purify bulk cooking oil is recommended, which can lead to more economically valuable products like soap bars.